2009
DOI: 10.1111/j.1439-0272.1993.tb02674.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium, lead, selenium, and zinc in semen of occupationally unexposed men

Abstract: Summary. Concentrations of cadmium, lead, selenium, and zinc were determined in semen and seminal plasma of 22 volunteers by atomic absorption spectrometry. Additionally conventional semen parameters and, by means of computer videomicrography, motion parameters of spermatozoa were evaluated. Concentrations of Cd, Pb, and Zn determined in semen were not significantly different from those measured in seminal plasma. However, selenium levels were significantly higher in semen (53.8 ± 22.9 μg 1−1) than in seminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 24 publications
1
22
0
5
Order By: Relevance
“…Seminal plasma cadmium levels have been reported to be unrelated to semen parameters and fertility status (71)(72)(73)(74), to be positively correlated with semen parameters (75), to increase as sperm concentration is decreased (76,77), and to be inversely related to semen parameters only in those men whose semen parameters are already adversely compromised (44,78,79). Our results showed an inverse correlation of seminal plasma cadmium levels with semen parameters in men from infertile couples (group 1) but not known fertile males (group 2) or volunteers from the general population (group 3).…”
Section: Discussionmentioning
confidence: 99%
“…Seminal plasma cadmium levels have been reported to be unrelated to semen parameters and fertility status (71)(72)(73)(74), to be positively correlated with semen parameters (75), to increase as sperm concentration is decreased (76,77), and to be inversely related to semen parameters only in those men whose semen parameters are already adversely compromised (44,78,79). Our results showed an inverse correlation of seminal plasma cadmium levels with semen parameters in men from infertile couples (group 1) but not known fertile males (group 2) or volunteers from the general population (group 3).…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies have been adjusted for the infl uence of age and current smoking (66,(105)(106)(107)(108)(109), and for other metals (66,105,(107)(108)(109). Other studies (110)(111)(112)(113)(114) have not found any association between low-level lead exposure and semen quality or endocrine function in men.…”
Section: Effects Of Environmental Exposure To Metals On Reproductive mentioning
confidence: 99%
“…A study of Singapore men did not find correlations between blood or seminal plasma lead levels and sperm concentration, motility, or morphology [Xu et al 1993], but did not adjust for potential confounders, including cigarette smoking, a potential source of lead exposure. Another small study of 22 German volunteers with mean semen lead level of 98 mg/L did not find significant correlations between lead level and sperm parameters [Noack-Fuller et al 1993]. The population was not described and there was no adjustment for potential confounders.…”
Section: Animal and In-vitro Studiesmentioning
confidence: 99%